Engaging the Public to Identify Opportunities to Improve Critical Care: A Qualitative Analysis of an Open Community Forum. - Melissa L Potestio; Jamie M Boyd; Sean M Bagshaw; Daren Heyland; Peter Oxland; Christopher J Doig; Dave Zygun; Henry T Stelfox (PLoS ONE, 2015)
To engage the public to understand how to improve the care of critically ill patients.A qualitative content analysis of an open community forum (Café Scientifique).Public venue in Calgary, Alberta, Canada.Members of the general public including patients, families of patients, health care providers, and members of the community at large.A panel of researchers, decision-makers, and a family member led a Café Scientifique, an informal dialogue between the populace and experts, over three-hours to engage the public to understand how to improve the care of critically ill patients. Conventional qualitative content analysis was used to analyze the data. The inductive analysis occurred in three phases: coding, categorizing, and developing themes.Thirty-eight members of the public (former ICU patients, family members of patients, providers, community members) attended. Participants focused the discussion and provided concrete suggestions for improvement around communication (family as surrogate voice, timing of conversations, decision tools) and provider well-being and engagement, as opposed to medical interventions in critical care.Café participants believe patient and family centered care is important to ensure high-quality care in the ICU. A Café Scientifique is a valuable forum to engage the public to contribute to priority setting areas for research in critical care, as well as a platform to share lived experience. Research stakeholders including health care organizations, governments, and funding organizations should provide more opportunities for the public to engage in meaningful conversations about how to best improve healthcare.